A CARLEMAN'S INEQUALITY FOR A SYSTEM OF COUPLED PARABOLIC EQUATIONS - Cabanillas Zannini, Víctor Rafael (2009)
In this work we consider a linearized system of parabolic equations associated to a semilinear system of heat equations. Following the ideas of O. Imanuvilov, M. Yamamoto and L. de Teresa we prove a estímate of Carleman type for a system of parabolic equations involving gradient terms. This class of systems appears in the treatment of controls insensitizing the norm of the solution of a semilinear heat equation.